RELATIONSHIP SUPPORT OF WORK PLACES WITH EXCLUSIVE BREASTFEEDING ON WORKING MOTHERS - Mina Yumei Santi; Sabar Santoso; Nasyiatush Sholihah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
The United Nation Children's Fund and World Health Organization recommend exclusive breastfeeding to reduce infant mortality and morbidity. Working mothers tend not to breastfeed exclusively compared to mothers who do not work or housewives. Lack of workplace support is one of the factors causing exclusive breastfeeding failure on working mothers. In the area of Puskesmas Sewon II, exclusive breastfeeding coverage decreased from 2015 to 2016 and became one of the lowest coverage centers in Bantul Regency. The aim of the study is to determine the relationship of workplace support with exclusive breastfeeding on working mothers in the working area of Puskesmas Sewon II. The research method was analytical observation with cross sectional design. Purposive sampling technique was demonstrated and obtained 70 working mothers. Data collection used questionnaires that had been tested for its validity and reliability. Data were analyzed using chi-square. The result indicated that there was a relationship between workplace support and exclusive breastfeeding on working mothers with p-value 0.011 (α = <0.05) and low close relationship with coefficient contingency 0.291. Characteristics of respondents related to exclusive breastfeeding were education, parity and duration of work. The workplace is expected to provide time, facilities and policies that support exclusive breastfeeding of working mothers in accordance with government regulations.